Microfinancing, Preference and Loyalty Analysis: A Study of Islamic Microfinance Institutions in Indonesia - Riduwan; Amrullah; Danupranata, Gita; Wahyudi, Rofiul (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to analyse people's preferences and loyalty to using microfinance. The research utilised a descriptive qualitative method by conducting in-depth interviews with microbusinesses and stakeholders. The research population comprised microfinance users with a sample size of 186 people from various regions in Indonesia, along with 18 people from the management of Islamic microfinance institutions. The results of the research suggest that preferences and loyalty in using microfinance are mostly influenced by the speed of service, ease of procedures, and personal relationships. Apart from that, the belief that business owners are free from usury (riba) is also a determining factor in choosing Islamic microfinance despite the higher cost. The findings also show that micro-business owners receive social benefits in the form of mentoring to help develop their businesses. The results of this study provide a significant contribution to understanding the factors that influence people's preferences and their loyalty to using microfinance. The research results can provide a valuable basis for stakeholders to formulate financing policies that are more suitable to the needs and conditions of the community and micro businesses.